2018
DOI: 10.1021/acs.langmuir.8b01233
|View full text |Cite
|
Sign up to set email alerts
|

On the Oblique Impact Dynamics of Drops on Superhydrophobic Surfaces. Part II: Restitution Coefficient and Contact Time

Abstract: We tested oblique drop impacts on a superhydrophobic surface at normal Weber numbers ( We) in the range of 3-45, and at varying angles of incidence (AOIs), ranging from 0° (normal impact) to 60° (highly oblique). Our objective is to define the influence of the AOI on the restitution coefficient and on the contact time of rebounding droplets. To interpret the overall restitution coefficient of oblique drop rebounds (ε), we decoupled it into two separate components: a normal (ε) and a tangential restitution coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 27 publications
(103 reference statements)
2
43
1
1
Order By: Relevance
“…Compared to normal impact, more attention has been given to oblique impact for practical application [107][108][109][110][111]. A droplet in oblique impact is subject to a combination of downward motion along the surface with a tangential impinging velocity of v 0 sinf and motion normal to the surface with an impinging velocity of v 0 cosf, where v 0 is the impact velocity and f is the tilt angle of the surface.…”
Section: Collision On Sophisticated Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to normal impact, more attention has been given to oblique impact for practical application [107][108][109][110][111]. A droplet in oblique impact is subject to a combination of downward motion along the surface with a tangential impinging velocity of v 0 sinf and motion normal to the surface with an impinging velocity of v 0 cosf, where v 0 is the impact velocity and f is the tilt angle of the surface.…”
Section: Collision On Sophisticated Interfacesmentioning
confidence: 99%
“…7c. This is explained by the asymmetric drop deformation during a collision and asymmetric bouncing mechanism to reduce the contact time [70,110]. On another note, oblique bouncing or migration can occur on the horizontally placed surface but with wetting or thermal gradient due to the unbalanced interfacial forces created by such heterogeneous architectures [113][114][115][116].…”
Section: Collision On Sophisticated Interfacesmentioning
confidence: 99%
“…In nature and industrial fields, the droplet encounters various solid surface, such as curve, textured, and inclined surface [24][25][26][27][28][29][30][31][32][33][34]. Compared with the flat horizontal surface, the outcomes are more complex, and the results may be different.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that the droplet impacting an inclined surface behaves asymmetry between the tangential and lateral direction along the surface, which can promote the droplet to rebound from the surface. Meanwhile, due to the tangential velocity, the droplet slides along the inclined surface, away from the impact position [31][32][33]. If two droplets impact an inclined surface successively, the off-center impact should be observed, which is different from horizontal surface and still poorly understood, especially on superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Кристаллизация растворенных в переохлажденной воде кристаллов описывается уравнением Кана-Хиллиарда [3] = ∇ • ( )∇ ( ) − ∆ ⁄ (здесь концентрация кристаллов, -коэффициент градиента энергии, = ( ) -коэффициент подвижности, ( ) -гомогенная свободная энергия) и уравнением Гинсбурга-Ландау; при исследовании процессов кристаллизации используется теория неустойчивости Муллинс-Cикерки [4]. Данные об особенностях кристаллизации переохлажденной воды получены в предшествующих исследованиях [5][6][7][8]. Стремление понять внутреннюю структуру воды возрастает тем более, чем больше накапливается фактов о ее разнообразных проявлениях [9][10][11][12].…”
unclassified